2015
DOI: 10.23955/rkl.v10i4.3772
|View full text |Cite
|
Sign up to set email alerts
|

Sintesis dan Karakterisasi Membran Poliuretan dari Minyak Biji Karet dan Heksametilen-1,6-diisosianat

Abstract: Minyak biji karet dapat dimanfaatkan untuk pembuatan membran poliuretan. Minyak biji karet memiliki bilangan hidroksi 40,33 mgKOH/g dan bilangan iod 154,05 gI2/g. Sintesis membran poliuretan menggunakan metode ikatan silang. Ikatan silang terbentuk dengan mereaksikan minyak biji karet sebagai sumber gugus -OH dengan heksametilen-1,6-diisosianat sebagai sumber gugus -NCO.  Membran poliuretan yang optimum dihasilkan pada komposisi 4,55:5 (g/g) memiliki sifat homogen, kering, elastis, berwarna kuning kecoklatan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Polyurethane membranes have many advantages, including minimal energy usage, not requiring additional chemical substances [5], and strong chemical resistance [6], making it viable in extreme pH conditions; additionally, the membrane is very easy to apply, practical, and straightforward [3]. The use of natural materials as raw materials for the manufacture of polyurethane membranes has been widely developed, such as the use of castor oil [7] and carrageenan [8], as well as many other materials that have been developed for the synthesis of polyurethane membranes. Previous studies have reported results on the synthesis of polyurethane membranes from various types of base materials used for various applications, such as a research report from Huang and Lai in 1995, which stated that membranes derived from hydroxy-terminated polybutadiene (HTPB) and 4,4'-diphenylmethane diisocyanate (MDI) and 2,4-toluene diisocyanate (TDI) with various polyols had been used for oxygen gas separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane membranes have many advantages, including minimal energy usage, not requiring additional chemical substances [5], and strong chemical resistance [6], making it viable in extreme pH conditions; additionally, the membrane is very easy to apply, practical, and straightforward [3]. The use of natural materials as raw materials for the manufacture of polyurethane membranes has been widely developed, such as the use of castor oil [7] and carrageenan [8], as well as many other materials that have been developed for the synthesis of polyurethane membranes. Previous studies have reported results on the synthesis of polyurethane membranes from various types of base materials used for various applications, such as a research report from Huang and Lai in 1995, which stated that membranes derived from hydroxy-terminated polybutadiene (HTPB) and 4,4'-diphenylmethane diisocyanate (MDI) and 2,4-toluene diisocyanate (TDI) with various polyols had been used for oxygen gas separation.…”
Section: Introductionmentioning
confidence: 99%
“…The polyurethane membrane produced has an elongation percentage of 9%, a tensile strength of 340 kgf/mm 2 , a glass transition temperature of 243.6 • C, and a melting point of 423.02 • C. The polyurethane membrane has elastic, transparent, and strong properties, with a rejection factor of 45.9% and a flux value of 39.2 L/h.m 2 . The membrane was applied to the ultrafiltration process of 1000 ppm dextran solution [8]. Polyurethane membranes from natural materials have better performance when compared to membranes from commercial polyurethane materials.…”
Section: Introductionmentioning
confidence: 99%
“…This technology continues to develop due to its high selectivity properties [4][5] as well as its ability to be easily synthesized and applied [6][7]. One of the commonly developed membranes is polyurethane [8], which is a type of polymer membrane composed of urethane bonds [9] and formed from the reaction between compounds containing two or more reactive hydroxyl and isocyanate groups [10][11][12]. Polyurethane membranes can be synthesized using natural materials, such as carrageenan, which has strong and slightly elastic properties with a tensile strength of 340 kgf/mm 2 , at a 9% elongation percentage [13].…”
Section: ■ Introductionmentioning
confidence: 99%
“…PUM can be synthesized by using various natural materials such as castor oil [ 9 ], rubber seed oil [ 10 ], avocado seed oil [ 11 ], nyamplung seed oil [ 12 ], and carrageenan [ 13 ]. The natural materials, which contain a large amount of hydroxy (-OH) groups, can form urethane bonds with a source of isocyanate (-NCO) [ 10 , 14 , 15 ]. Selected natural materials that contain many hydroxy groups are red seaweed [ 8 , 16 ] and isolated carrageenan from seaweed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%